2021
DOI: 10.1177/23259671211017880
|View full text |Cite
|
Sign up to set email alerts
|

Bone Staples Provide Favorable Primary Stability in Cortical Fixation of Tendon Grafts for Medial Collateral Ligament Reconstruction: A Biomechanical Study

Abstract: Background: The use of the interference screw (IFS) for the cortical fixation of tendon grafts in knee ligament reconstruction may lead to converging tunnels in the multiligament reconstruction setting. It is unknown whether alternative techniques using modern suture anchor (SA) or bone staple (BS) fixation provide sufficient primary stability. Purpose: To assess the primary stability of cortical fixation of tendon grafts for medial collateral ligament (MCL) reconstruction using modern SA and BS methods in com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The anatomy of porcine knees was shown to be sufficiently similar to that of human knees, 46 and porcine flexor tendons possess biomechanical properties similar to those of human hamstring tendons, 17 making it a frequently used model to assess the biomechanical primary stability of orthopaedic implants. 19,23,24,43 Nevertheless, bone density in the porcine model is significantly higher in comparison with humans, 1 which could have affected the findings of the present study. 8,42 A recent study showed that, in a test setup like that used in this study, the displacement of the machine actuator used to calculate the elongation was significantly higher than the actual graft slippage, as measured by optical tracking at the tunnel aperture, although both values were highly correlated.…”
Section: Limitationsmentioning
confidence: 69%
“…The anatomy of porcine knees was shown to be sufficiently similar to that of human knees, 46 and porcine flexor tendons possess biomechanical properties similar to those of human hamstring tendons, 17 making it a frequently used model to assess the biomechanical primary stability of orthopaedic implants. 19,23,24,43 Nevertheless, bone density in the porcine model is significantly higher in comparison with humans, 1 which could have affected the findings of the present study. 8,42 A recent study showed that, in a test setup like that used in this study, the displacement of the machine actuator used to calculate the elongation was significantly higher than the actual graft slippage, as measured by optical tracking at the tunnel aperture, although both values were highly correlated.…”
Section: Limitationsmentioning
confidence: 69%
“…Our previous investigation 9 revealed the promising biomechanical stability of BSs for cortical fixation of MCL grafts in comparison with interference screw fixation and suture anchor fixation in the same porcine knee model: no statistical differences in elongation during cyclic loading or peak failure load were found between narrow BSs with spikes (3.4 ± 1.0 mm and 376 ± 120 N, respectively) and interference screw fixation (3.9 ± 1.2 mm and 313.0 ± 99.5 N, respectively), whereas graft fixation with a single suture anchor was found to have significantly more elongation during cyclic loading (6.4 ± 0.9 mm) and a lower peak failure load (228 ± 49 N). 9 Omar et al 25 compared the biomechanical stability of 4.0-mm cancellous screws with different washers as well as single or double titanium suture anchors in a porcine knee model of MCL reconstruction. Spiked polyetheretherketone washers with polyester sutures resulted in the most favorable biomechanical properties for both elongation during cyclic loading (2.9 ± 0.7 mm) and ultimate failure load (470 ± 64 N).…”
Section: Discussionmentioning
confidence: 97%
“…An a priori power analysis showed that a sample size of 10 per group would yield 90% power to detect a difference of 50 N between group means of peak failure load at the f ≥ 0.8 level based on the standard deviations of MCL graft fixation methods in porcine knee models in previous studies. 9 , 25 The normal distribution was evaluated using the Shapiro-Wilk test. The Kruskal-Wallis test was used to compare groups, and the post hoc Dunn test was performed for multiple comparisons.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Recent studies have investigated the concept of onlay fixation using different metal or soft tissue anchors. 8,19,21 Clinical studies comparing onlay and intraosseus screw fixation are missing, but a recent animal study examined the biological properties of an onlay MCL fixation, which demonstrated nonsignificant differences when compared with the native MCL. 35 These results are in line with clinical data showing good to excellent results of ligament fixation using the anchor technique.…”
Section: Discussionmentioning
confidence: 99%